Competition and demography rather than dispersal limitation slow down upward shifts of trees' upper elevation limits in the Alps. (20th July 2020) - Scherrer, Daniel; Vitasse, Yann; Guisan, Antoine; Wohlgemuth, Thomas; Lischke, Heike
Abstract: Species range limits are expected to be dramatically altered under future climate change and many species are predicted to shift their distribution upslope to track their suitable conditions (i.e. based on their niche). However, there might be large discrepancies between the speed of the upward shift of the climatic niche and the actual migration velocity of the species, especially in long‐lived organisms such as trees. In fact, most studies did not find any significant upward shift of the distributional limits of temperate forest trees over the last decades. It therefore beckons the questions why trees are moving upslope much slower than their bioclimatic envelope and what are the implications for ecosystem functioning. Here, we compared the simulations of the upslope displacement of the bioclimatic envelope of 16 tree species inhabiting temperate mountain forests under ongoing and future climate change obtained by correlative species distribution models (SDMs) to those from a dynamic forest model accounting for dispersal, competition and demography. We then partitioned the discrepancy in upslope migration velocity between the SDMs and the dynamic forest model into different components by manipulating dispersal limitation, interspecific competition and demography. Tree species in the dynamic forest model migrated only slowly upslope in contrast to the SDMs. Most of the difference in migration velocity can directly be attributed to tree's demography (long life cycle), followed by effects of competition and only a marginal contribution of dispersal limitation. Additionally, lower elevation species ('non‐treeline') shifted slower upslope than high elevation species ('treeline') indicating a strong effect of interspecific competition at their leading edge. Synthesis . Forests have a high inertia to climate change because of their longevity and ability to acclimatize to high climatic fluctuations. Lower elevation tree species (deciduous) only slowly establish in stands at higher elevation where coniferous species dominate and likely profit from facilitation by disturbance events. Therefore, forest ecosystems seem to persist, even if climate becomes unfavourable, until they approach a tipping point at which an extreme event (e.g. drought, storm or insect attack) leads to a large dieback and resource change enabling new suitable species to spread and establish. Abstract : Forests have a high inertia to climate change because of their longevity and ability to acclimatize to high climatic fluctuations. Lower elevation tree species (deciduous) only slowly establish in stands at higher elevation where coniferous species dominate and likely profit from facilitation by disturbance events. Here, comparing predictions from bioclimatic envelopes to those of dynamic forest models, we show that the upper elevational limits of trees in the Alps moves much slower than their climatic potential as a result of demographic processes and inter‐specific competition at their leading edge rather than due to dispersal limitations.